Measuring methods of the efficiency of university technology transfer - Bartha, Klára (Acta Agraria Debreceniensis, 2014)
Nowadays, the socio-economic role and function of universities as well as their relationship with the industry, are more than ever in the focus of both the political and the academic spheres. The importance of knowledge and technology transfer is increasingly stressed in various economic development plans and strategies. The increased interest is due to the fact that universities are located at the crossroads of education, research and innovation, which might be crucial for the country's economic competitiveness. The commercialization of university research results is a well-defined task of technology transfer offices. Measuring the efficiency and successfulness of such offices is a difficult, but not impossible task. The present article aims to analyze the existing literature on measuring the efficiency of technology transfer activities and to introduce the most commonly used measuring methods of effective technology transfer. The article attempts to answer the question how to measure the efficiency of technology transfer by reviewing the available international literature and by analyzing secondary data.